(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
It is known that microscopic algae contain a variety of valuable substances, such as protein, carbohydrates, fats, vitamins, minerals. Especially in the use of algae as a nutrient, the protein in it plays an important role, in which it is important to preserve all amino acids, including non-exchangeable amino acids. With this in mind, algae have been used in various fields. In our study, the biomass of chlorella and chlamydomonas in fur-bearing animals was previously tested as a biostimulator, and it was found that mink had a positive effect on the growth and development of nutria animals and the quality of their fur.